Analisis Pengaruh Produk, Harga, Promosi dan Lokasi Terhadap Keputusan Pembeli Di PT. Dimensi Putra Mandiri Colomadu Karanganyar - Ngaisah Ngaisah; MG Sukamdiani; Pipit Tri Fatiâ€™ah (JURNAL WIRANOMIKA, 2022)
This study aims to determine the effect of the product, price, promotion, and place of purchasing decisions at PT Dimensi Putra Mandiri Colomadu Karanganyar. The independent variable are product, price promotion, and place affect the purchase decision as the dependent variable. The population in this study are customers PT Dimensi Putra Mandiri. Samples were taken of 100 respondents using a random sampling technique. Data was collected using a survey method through questionnaires filled out by customers. Then, the data obtained were analyzed using multiple regression analysis. This analysis includes the validity test, reliability test, hypothesis testing through the F test and t test, and coefficient of determination analysis (RÂ²). Based result, obtained regression equation: Y = 1,693 + 0,202X1+ 0,484X2 + 0,147X3+ 0,081X4. Based on statical data analysis, the indicators in this research is valid and the variables are reliable. Individually, the variables have greater influence is price with the regression coefficient 0,484, followed by the product variable with a regression coefficient 0,202, promotion 0,147 and the variable have the negative influence is place with the regression coefficient 0,081. The computation of hypothesis using the t test showed that the variable product and promotion in meticulous proved significant. And the variable price and place not significantly influence the purchase decision variables. Then through the F test can be know that the independent variable is feasible to test purchasing dependent variable. Figures adjusted R square of 0,849 indicates that variable of purchasing decision can be explained by four independent variables in the regression quotation. The remaining 15,1% is explained by other variable out side of the three variables used in this research.Key word : Purchasing Decisions, Product, Price, Promotion, Place